The anthropogenic refuge areas for bee flora in agricultural landscape - Bożena Denisow (Acta Agrobotanica, 2012)
The investigations were carried out in 2002-2006 in two municipalities of Konopnica and Jastków close to the western part of Lublin, Poland. The aim of the study was to identify the condition of bee flora and determine the floristic richness depending on the biotops in agricultural landscape. Flora of the anthropogenic refuge areas consists of 214 species, among them 80% were flow taxons. Apophytes (162 species - 78%) predominated on all types of biotops under consideration. Perennials predominated in flora of boundary strips and bush communities. Mainly annual (40%) and biennial (15%) species comprise the flora of fallows. A great number of bee taxons represent meadow, segetal or ruderal communities. Most of flow plants compose loose patches, but their successive blooming ensures a source of food for Apoidea from early spring till the end of summer. The flora of boundary strips, bush communities and fallows significantly increases the biodiversity in agricultural landscape. The treatments including sowing, mainly on fallows with nectariferous and polleniferous species, would enrich generally weak flows in highly agricultural landscape.